Pregnancy outcome following maternal exposure to statins: a multicentre prospective study. Issue 4 (30th November 2012) - Winterfeld, U; Allignol, A; Panchaud, A; Rothuizen, LE; Merlob, P; Cuppers‐Maarschalkerweerd, B; Vial, T; Stephens, S; Clementi, M; De, M; Pistelli, A; Berlin, M; et al.
<x xml:space="preserve">Abstract</x> Objective This contribution addresses the risk associated with exposure to statins during pregnancy. Design Multicentre observational prospective controlled study. Setting European Network of Teratology Information Services. Population Pregnant women who contacted one of 11 participating centres, seeking advice about exposure to statins during pregnancy, or to agents known to be nonteratogenic. Methods Pregnancies exposed during first trimester to statins were followed up prospectively, and their outcomes were compared with a matched control group. Main outcome measures Rates of major birth defects, live births, miscarriages, elective terminations, preterm deliveries and gestational age and birthweight at delivery. Results We collected observations from 249 exposed pregnancies and 249 controls. The difference in the rate of major birth defects between the statin‐exposed and the control groups was small and statistically nonsignificant (4.1% versus 2.7% odds ratio [OR] 1.5; 95% confidence interval [95% CI] 0.5–4.5, P = 0.43). In an adjusted Cox model, the difference between miscarriage rates was also small and not significant (hazard ratio 1.36, 95% CI 0.63–2.93, P = 0.43). Premature birth was more frequent in exposed pregnancies (16.1% versus 8.5%; OR 2.1, 95% CI 1.1–3.8, P = 0.019). Nonetheless, median gestational age at birth (39 weeks, interquartile range [IQR] 37–40 versus 39 weeks, IQR 38–40, P = 0.27) and birth weight (3280 g, IQR 2835–3590 versus 3250 g, IQR 2880–3630, P = 0.95) did not differ between exposed and non‐exposed pregnancies. Conclusions This study did not detect a teratogenic effect of statins. Its statistical power remains insufficient to challenge current recommendations of treatment discontinuation during pregnancy.